MicroRNAs as regulators in plant metal toxicity response - Mendoza-Soto, Ana B.; Sanchez, Federico; Hernandez, Georgina (Frontiers in Plant Science, 2012)
Metal toxicity is a major stress affecting crop production. This includes metals that are essential for plants (copper, iron, zinc, manganese), and non-essential metals (cadmium, aluminum, cobalt, mercury). A primary common effect of high concentrations of metals such as aluminum, cooper, cadmium or mercury, is root growth inhibition. Metal toxicity triggers the accumulation of reactive oxygen species leading to damage of lipids, proteins and DNA. The plants response to metal toxicity involves several biological processes that require fine and precise regulation at transcriptional and post-transcriptional levels. MicroRNAs (miRNAs) are 21 nucleotides non-coding RNAs that regulate gene expression at the post-transcriptional level. A miRNA, incorporated into a RNA induced silencing complex, promotes cleavage of its target mRNA that is recognized by an almost perfect base complementarity. In plants miRNA regulation has been involved in development and also in biotic and abiotic stress responses. We review novel advances in identifying miRNAs related to metal toxicity responses and their potential role according to their targets. Most of the targets for plant metal-responsive miRNAs are transcription factors. Information about metal-responsive miRNAs in different plants points to important regulatory roles of miR319, miR390, miR393 and miR398. The target of miR319 is the TCP transcription factor, implicated in growth control. MiR390 exerts its action through the biogenesis of trans-acting small interference RNAs that, in turn, regulate auxin responsive factors. MiR393 targets the auxin receptors TIR1/AFBs and a bHLH transcription factor. Increasing evidence points to the crucial role of miR398 and its targets Cu/Zn superoxide dismutases in the control of the oxidative stress generated after high metal copper or iron exposure.